Hepatosplenic T-cell Lymphoma with Aberrant Expression of Serum β-HCG: A Case Report. Issue 6 (November 2015) - Bellodi, Andrea; Rivoli, Giulia; Arboscello, Eleonora; Fornarini, Giuseppe; Orcioni, Giulio Fraternali; Avenoso, Daniele; Miglino, Maurizio; Ghio, Riccardo
Background: Peripheral T-cell lymphomas (PTCL) represent a heterogeneous group of hematologic malignancies frequently presenting at advanced stage of diagnosis. Methods: We report a case of PTCL with an uncommon and aggressive onset with disseminated intravascular coagulation (DIC). Results: Laboratory findings revealed an aberrant expression of β subunit of human chorionic gonadotropin (β-HCG). Other than for determination of pregnancy, β-HCG is regularly found as a tumor marker in germ cell tumors with trophoblastic differentiation and its aberrant expression has been reported in the literature in other neoplastic conditions only in the context of case reports. Conclusions: In hematologic malignancies, β-HCG expression has been described only in sporadic cases. Awareness of this feature could avoid diagnostic delay in such an aggressive disease.